2018
DOI: 10.1002/acn3.574
|View full text |Cite
|
Sign up to set email alerts
|

Altered dynamics of neurovascular coupling in CADASIL

Abstract: Background and ObjectiveNeurovascular coupling is the complex biological process that underlies use‐dependent increases in blood flow in response to neural activation. Neurovascular coupling was investigated at the early stage of CADASIL, a genetic paradigm of ischemic small vessel disease.MethodsFunctional hyperemia and evoked potentials during 20‐ and 40‐sec visual and motor stimulations were monitored simultaneously using arterial spin labeling‐functional magnetic resonance imaging (ASL‐fMRI) and electroenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Experimental studies have amply demonstrated that hypertension and aging, 2 leading risk factors for VaD and SVD, have profound impact on vessel wall structure and CBF regulation (57,58). Recent human studies using BOLD or arterial spin labeling-MRI provided convincing evidence that cerebrovascular reactivity is altered in patients with SVD (59,60). Moreover, a recent post-mortem study in patients with VaD showed that endothelium-dependent arteriolar dilation was significantly reduced in the WM-penetrating arterioles (61).…”
Section: Pathobiologymentioning
confidence: 99%
“…Experimental studies have amply demonstrated that hypertension and aging, 2 leading risk factors for VaD and SVD, have profound impact on vessel wall structure and CBF regulation (57,58). Recent human studies using BOLD or arterial spin labeling-MRI provided convincing evidence that cerebrovascular reactivity is altered in patients with SVD (59,60). Moreover, a recent post-mortem study in patients with VaD showed that endothelium-dependent arteriolar dilation was significantly reduced in the WM-penetrating arterioles (61).…”
Section: Pathobiologymentioning
confidence: 99%
“…Importantly, disturbances in blood flow and the processes that regulate it are increasingly appreciated to play a key role in a variety of pathological conditions. These include dementias such as Alzheimer's disease (AD) (Alsop et al, 2000;Iadecola, 2004;Nicolakakis and Hamel, 2011;Iturria-Medina et al, 2016), small vessel disease of the brain (Dabertrand et al, 2015;Capone et al, 2016;Huneau et al, 2018), psychological conditions such as schizophrenia (Mathew et al, 1988;Zhu et al, 2017) and chronic stress (Longden et al, 2014;Han et al, 2019), plus diabetes (Mogi and Horiuchi, 2011;Vetri et al, 2012), hypertension (Girouard and Iadecola, 2006;Capone et al, 2012), and stroke (Girouard and Iadecola, 2006;Koide et al, 2012;Balbi et al, 2017), and pericytes appear to be exceptionally sensitive to pathological perturbations (Winkler et al, 2011).…”
Section: Control Of Pericyte V M By Pericyte Ion Channels and Gpcrs-cmentioning
confidence: 99%
“…Cerebral hypoperfusion, particularly in the white matter, has been documented in sporadic SVDs and CADASIL, although it is not yet clear whether a reduction in CBF is a causative factor or a secondary response to the reduced metabolic demand of the injured brain (41). Furthermore, functional MRI studies have provided convincing evidence that cerebrovascular reactivity-the CBF increase in response to neuronal activation or a vasodilatory stimulus, such as inhaled carbon dioxide (CO2)-is an early alteration in patients with sporadic SVD or CADASIL (40,42).…”
Section: Reduced Cerebral Blood Flowmentioning
confidence: 99%